RADIOLOGICAL FINDING OF PNEUMOMEDIASTINUM AS A RARE COMPLICATION OF EMPHYSEMATOUS PYELONEPHRITIS - Mijović, Ksenija; Stanišić, Nevena; Mašulović, Dragan; Šaponjski, Dušan; Bogosavljević, Nikola; Vasin, Dragan; Mitrović Jovanović, Milica (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Emphysematous pyelonephritis is a rare, acute, and life-threatening necrotizing renal infection caused by gas-producing facultative anaerobes, such as Escherichia coli, Klebsiella, and Proteus, most commonly in the setting of underlying diabetes mellitus. Pneumomediastinum is a rare imaging finding in this disease, and a high index of suspicion is required for diagnosing emphysematous pyelonephritis in patients presenting with pneumomediastinum, in the right clinical setting. Case presentation: We present the case of a middle-aged female patient with symptoms and laboratory findings indicating infection, renal failure, and hyperglycemia, and a personal history of diabetes mellitus. The imaging procedures revealed findings of a severe and advanced necrotizing renal infection with parenchymal destruction and intraparenchymal gas collections extending into the perirenal and pararenal spaces. We established the diagnosis of emphysematous pyelonephritis accompanied by perirenal abscess formation and pneumoretroperitoneum, with gas collections propagating into the mediastinum. In the setting of such a severe form of infection, the patient underwent immediate surgery with left nephrectomy. Despite prompt and intensive treatment, the patient unfortunately succumbed to the disease during the postoperative period. Conclusion: Pneumomediastinum is a rare complication of retroperitoneal processes, and, when present, indicates their extensiveness, often being an ominous prognostic sign. By presenting this case, we aim to highlight the severity of this form of renal infection and the unequivocal need for immediate response, as well as to emphasize the significance of imaging findings, which are somewhat unusual, but should raise suspicion of an insidious and serious retroperitoneal infection.